2000
DOI: 10.4269/ajtmh.2000.62.698
|View full text |Cite
|
Sign up to set email alerts
|

Limited potential for transmission of live dengue virus vaccine candidates by Aedes aegypti and Aedes albopictus.

Abstract: Abstract. To evaluate the transmission risk of four live dengue (DEN) vaccine candidates developed by the U. S. Army (DEN-1, 45AZ5 PDK 20; DEN-2, S16803 PDK 50; DEN-3, CH53489 PDK 20; and DEN-4, 341750 PDK 20), we tested 3,010 Aedes aegypti and 1,576 Aedes albopictus mosquitoes blood-fed on 21 volunteers who had been administered one of the four vaccine candidates or the licensed yellow fever (YF) vaccine (17D). We used an indirect immunofluorescence assay (IFA) to detect DEN or YF viral antigen in the heads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Both host and viral determinants of dengue replication may affect viremia and thus contribute to the transmission potential of the virus to the mosquito. Some attenuated vaccine candidates have been shown to exhibit limited dissemination potential in mosquitoes (27,29,54,57). Specifically, a 30-nt deletion in the 3Ј ntr was shown to disrupt the ability of dengue virus to disseminate to the salivary gland after ingestion of a virus-spiked blood meal (57).…”
Section: Discussionmentioning
confidence: 99%
“…Both host and viral determinants of dengue replication may affect viremia and thus contribute to the transmission potential of the virus to the mosquito. Some attenuated vaccine candidates have been shown to exhibit limited dissemination potential in mosquitoes (27,29,54,57). Specifically, a 30-nt deletion in the 3Ј ntr was shown to disrupt the ability of dengue virus to disseminate to the salivary gland after ingestion of a virus-spiked blood meal (57).…”
Section: Discussionmentioning
confidence: 99%
“…7 Previously, our group has reported that mosquitoes feeding on 17 of our monovalent vaccine volunteers resulted in rates of disseminated infection by the four serotype vaccine strains of 0.5%, 0.3%, <0.1%, and <0.1%, respectively. 33 The low rates of viremia by our attenuated viruses preclude the use of virus isolation as evidence of vaccine take. In the absence of measurable viremia, it is difficult to determine vaccine take due to the crossreactivity of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] It is critical that live-attenuated dengue vaccine viruses will not be transmitted by mosquitoes from vaccinees to the unvaccinated population, and part of the vaccine safety evaluation requires confirmation of low mosquito transmission potential. [13][14][15][16][17][18] To be transmissible by mosquitoes, the virus needs to be able to infect the mosquito midgut (infection), escape the midgut infection barrier, replicate in the salivary glands (dissemination), and be released into the mosquito saliva (transmission). 19 The TDV viruses were previously found to be inefficient at infection, dissemination, and transmission in Aedes aegypti, the primary vector of DENV.…”
Section: Introductionmentioning
confidence: 99%